Promoting patriotism, suppressing dissent views: the making of historical narratives and national identity in Russia and Poland - McGlynn, Jade; Thaidigsmann, Karoline; Frieß, Nina (Youth and memory in Europe, 2022)
Das Kapitel Promoting Patriotism, Suppressing Dissent Views: The Making of Historical Narratives and National Identity in Russia and Poland erschien in Youth and Memory in Europe auf Seite 221.
Gesehen am 27.07.2022